Physiological and Physicochemical Behavior of Soursop Fruits Refrigerated with 1‐Methylcyclopropene. Issue 1 (17th December 2012) - Espinosa, I.; Ortiz, R.I.; Tovar, B.; Mata, M.; Montalvo, E.
Abstract The effect of 1‐methylcyclopropene (1‐MCP) on the ripening of a native variety of soursop (Annona muricata L.) under refrigerated storage was evaluated. Control fruits were stored at 25 and 16C, and a group of fruits was exposed to 200 or 400 nL/L of 1‐MCP and then stored at 16C. The effect of 1‐MCP on soursop fruits stored at 16C (6 days) and then at 25C was also studied. Fruits stored at 25C ripened after 4–6 days. Fruits held at 16C ripened after 8–9 days; however, chilling injury symptoms were observed. 1‐MCP caused a reduction in respiration and ethylene production rates and there was no visible chilling injury to the fruit pulp. In conclusion, application of 200 or 400 nL/L of 1‐MCP on refrigerated soursop delayed ripening for 7 days, which should provide additional time to handle the fruit at least in the domestic market. Practical Applications Annonaceas are highly perishable fruits, and further investigation on postharvest handling is necessary because there is no postharvest treatment or technology available to preserve the fruits for more than 9 days. There are several studies on the application of 1‐methylcyclopropene (1‐MCP) in Annonaceas, but not all species have responded acceptably to 1‐MCP. Thus, more research on the application of 1‐MCP on unstudied varieties of Annonaceas is needed in order to explore the potential for the use of 1‐MCP. This study revealed that the application of 1‐MCP, followed by refrigerated storage, can lead to a 7‐day delay of the ripening process in the variety of soursop fruit grown in Nayarit, Mexico. This may contribute to an increase in availability and consumption, a reduction in postharvest losses and an increase in distribution of the soursop fruits in the national markets.